If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x(2 + -3) = xy Combine like terms: 2 + -3 = -1 14x(-1) = xy Reorder the terms for easier multiplication: 14 * -1x = xy Multiply 14 * -1 -14x = xy Solving -14x = xy Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1xy' to each side of the equation. -14x + -1xy = xy + -1xy Combine like terms: xy + -1xy = 0 -14x + -1xy = 0 Factor out the Greatest Common Factor (GCF), '-1x'. -1x(14 + y) = 0 Ignore the factor -1.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(14 + y)' equal to zero and attempt to solve: Simplifying 14 + y = 0 Solving 14 + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + y = 0 + -14 Combine like terms: 14 + -14 = 0 0 + y = 0 + -14 y = 0 + -14 Combine like terms: 0 + -14 = -14 y = -14 Add '-1y' to each side of the equation. y + -1y = -14 + -1y Combine like terms: y + -1y = 0 0 = -14 + -1y Simplifying 0 = -14 + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| -1/5-1/2v=-1/7 | | 7x^5/x^5 | | 3a+2b+c=n | | 2/3x-5=3 | | x^2+2xy+y^2-9=25 | | 5x^3-13x+20=0 | | (x-3).3+(2x-5).4+4x=0 | | 11x+19y=13 | | (y-24)+(3y-20)= | | 7!/(4)!3! | | 32.475+(4.87*30)= | | 12x/10y*4y/3xy | | 13x+14x+x=57 | | -10(2x+4)=-(-8-9x)+3x | | w-3.53=9.9 | | 4.2=t-5.4 | | -11(3)2(.12(-12))= | | v+5.84=8.29 | | (1/3)(27)= | | W+5.96=7.14 | | (a2)x1/2 | | p(3)=7!/(4)!3!*0.35^3*0.65^4 | | (3x+4)+(2x+9)=72 | | (2u-5v)(7u-3v+5)= | | 2=y/2.56 | | 1/2-(x-1)-1/3(x-2)+1/4(x-3)=2/3 | | lnx=1/9 | | 79-y=196 | | 1=12/t | | p/8=-16 | | 2lnx-1/3lny | | 3x^2+2xy+3y^2-7=0 |